The Pattern of Landholdings and Emerging Agrarian Relations: A Study in North Chotanagpur Region of India. Issue 1 (January 2015) - Behera, Hari Charan
In this paper, the author's attempt is to discuss about emerging landholding pattern, caste wise distribution of landholdings, caste-class relations based on the nature of landholdings, and other social issues concerning agrarian society in north Chotanagpur region of Jharkhand, India through a micro-level study. The focus in the paper is also about agrarian relations in the region through a caste based analysis.